Leadership, stress and burnout among basketball referees - Martínez-Moreno, A.; Ibáñez-Pérez, R.; Sánchez-Roca, C. (Journal of Human Sport & Exercise, 2021)
The study analyses leadership styles and their influence on burnout and stress among basketball referees, applying a non-probabilistic sampling, convenience sampling, to 61 referees, 85.2% men, 14.8% women. Descriptive analysis, correlations and hierarchical multiple regression models were performed. By applying the Multifactor Leadership Questionnaire MLQ-5, Inventario de Burnout en deportistas Revisado IBD-R [Revised Athlete Burnout Inventory], and Escala de Estrés en el Ámbito Deportivo EEAD [Stress Scale for Sports]. Moderate stress level (26-50) as well as burnout (50-60). Transformational leadership is associated with low levels of stress (p = .003) and high levels of personal accomplishment (p = .026). The developer style, inverse and significant effect (p = .013) with stress. Corrective leadership is associated with low levels of stress (p = .005) and high personal accomplishment (p = .019) and emotional exhaustion (p = .006) of burnout. Passive leadership is associated with high levels of stress (p = .013) and low levels of personal accomplishment (p = .023). As a conclusion, referees mainly apply transformational leadership associated with low levels of stress and high levels of personal accomplishment. They have moderate level of stress and burnout, while there are differences between those at the national level and those at the local-regional level, in addition there are differences regarding the role played, in relation to stress.